A model free approach to the pricing of downside risk in Argentinean stocks - José P. Dapena; Juan Andrés Serur; Julián R. Siri (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
The return dynamics of Argentina's main stock index, the SP Mer.Val., show a high level of volatility, signaling a higher degree of downside risk. To hedge against that specific risk, investors could buy put options. However, the Argentinean capital markets lacks variety of hedging contracts. The basic availability of put options depends on the possibility of short selling the underlying security, i.e. transfer risk to a third party, something not properly developed in the domestic market. Since data processing power has geometrically increased in the last decades and some mathematic formulas that were helpful for calculation had been surpassed by data gathering and processing that helps to find a better estimate when necessary, in this paper we show the point calculating protection against downside risk in the Argentinean stock market, using real data and programming an algorithm to perform calculations instead of resorting the standard Black-Scholes-Merton formulae, by means of a model free approach to acknowledge the issue.
Keywords: C1; C3; G11; 330; Asset pricing; options pricing; insurance; capital markets